GRAVIMETRIC TIDAL FACTORS AT SYOWA STATION OBTAINED FROM THREE-YEAR OBSERVATIONS WITH A SUPERCONDUCTING GRAVIMETER - タムラ, ヨシアキ; アオヤマ, ユウイチ; ナワ, カズナリ; TAMURA, Yoshiaki; AOYAMA, Yuichi; NAWA, Kazunari (National Institute of Polar Research, 1997)
P(論文) Gravity change observations with a superconducting gravimeter started in March 22,1993 at Syowa Station, Antarctica. The observations have been continuing almost four years until now. In this paper, the first three years of data are investigated for the purpose of obtaining detailed tidal constants for diurnal, semidiurnal and terdiurnal waves. The observed tidal constants show rather large δ factors of 1.2 and of 1.5 for diurnal and semidiurnal tides, respectively. Those apparent large δ factors could be explained by large ocean tide loading. After applying several corrections to the observed tidal parameters, the ocean-tide corrected tidal factors were compared with theoretical ones by an elastic, ellipsoidal, rotating Earth model. Finally, the obtained tidal factors are consistent with theoretical ones within the discrepancy of 1% for principal constituents. More detailed discussion, for example, to see the latitude dependency of tidal factors, awaits accurate calibration of the scale constant of the gravimeter. departmental bulletin paper